Measuring Sustainability of Kampong Tudong Riverside Settlements Using Urban Modeling Interface Simulation - Mutia Muyasarah; Arif Kusumawanto (Universitas Atma Jaya Yogyakarta, 2023)
Coastal settlements are the most vulnerable area to climate change, which has had an increasing impact on natural changes and human life in recent years. Therefore, sustainable riverside settlement models need to be developed by maximizing welfare with minimal environmental damage through modeling simulations that can help understand, compare and evaluate buildings and settlements. Simulation of Kampong Tudong on the banks of Kapuas River used Urban Modeling Interface to analyze the floor area ratio, daylighting, operational energy, and mobility. The simulation results show values of 0.21 on Floor Area Ratio, 30% on average natural resources for building daylighting, 86 kWh/m2year on operational energy, and 66 on mobility. Meanwhile, the efficient standard values are <3.2 on FAR, 55% on average daylighting, 10.08-30 kWh/m2.year on operational energy, and 90-100 on mobility. Existing simulation values indicate that these values can still be improved and maximized further for the sustainability of the riverside settlements.